MAIN ISSUES ABOUT QUALIFICATION CIRCUMSTANCES EXCLUDING CRIMINAL RESPONSIBILITY (Law and world, 2016)
Circumstances excluding criminal responsibility are actual forseveral reasons: lack of not guilty verdict; these issues are not theoriticaly processed in Georgian legal literature. That is why our research is dedicated to the circumstances excluding criminal responsibility. Definition of crime consists of three main steps: act, unlawfulness, guilt. Therefore, cirscumstances excluding criminal responsibility are devided in two main groups: Circumstances Excluding the Criminal nature of an action and Circumstances excluding and mitigating guilt. Artciles 32 and 38 of the Criminal Code of Georgia regulate issues connected with releasing from criminal liability for other legally justifiable acts and releasing from criminal liability for other non-culpable actions. These are cisrcumstances, which must be established by judicial practice. Unfortunately, there is no case law about these issues. With this thesis, we tried to make clear the essential issues about excluding criminal responsibility and we hope that the research will have an impact on the interpretation of articles 32 and 38.